Building A Comprehensive Conceptual Framework for Material Selection in Terms of Sustainability in The Construction Preliminary Design Phase - Dinh, Trong Hung; Dinh, Trung Hieu (International Journal of Sustainable Construction Engineering and Technology, 2021)
Construction projects consume a massive amount of renewable and non-renewable resources and negatively affect sustainable development. The selection of materials is necessary to meet the demands of sustainability. The preliminary design phase is essential within construction project phases because the main requirements, budget, and master drawings are planned here. Also, the selection of primary materials is considered in this phase. However, the integration of material selection and sustainability in the preliminary design phase has been underestimated. This paper reviewed sustainability in the preliminary design phase and the importance of material selection in accordance with sustainability in this phase. By using current literature and tools like Leadership in Energy and Environmental Design (LEED) and Building Research Establishment Environmental Assessment Method (BREEAM), the paper establishes a conceptual framework including sub-aspects that relate to sustainable aspects (economy, environment, and society). The proposed sus-aspects, such as total cost, cost efficiency, budget management, and water efficiency, define the relevant activities that help select the most sustainable materials. The results can be applied as a guide to decision-makers and promote sustainability right from the preliminary design phase. Future studies may provide methods for each criterion and establish a detailed plan to apply this framework in practice.